PELAKSANAAN TUGAS RESTAURANT SUPERVISOR PADA FOOD AND BEVERAGE SERVICE DEPARTEMENT DI HARRIS RESORT WATERFRONT BATAM - Ledi Yusi Hutasoit; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The implementation of Supervisor  is someone’s duty in an organization with responsibility to their position  namely arrange, control, and responsible to their own team or their employee. By Supervisor control, employee can work maximum  as well as the valid standart operasional produre The aim of this research is to know the implementation of  Restaurant Supervisor duties in FnB at Harris Resort Waterfront Batam, to know the implementation of Restaurant Supervisor duty on administration and to know the implementation of Restaurant Supervisor duty on operational. This research method is qualitative method. Key Informan of this research is one that is Restaurant Supervisor and four additional informan from Food and Beverage Service Departement namely FnB Captain, Waiter and  Bartender. The data collection are interview, observation and documentation. The result of this research will uncover the implementation of Restaurant Supervisor duties in Food and Beverage Service Departement at Harris Resort Waterfront Batam. It will also uncover the implementation of Restaurant Supervisor duty on administration like make a daily schedule, make monthly promotion, make puchasing request, market list and store request. Also uncover the implementation of Restaurant Supervisor duty on operational like lead the daily briefing, handling complaint, and control daily general cleaning.  Keyword: Supervisor’s Implementation, Food and Beverage Service Departement, Administration, Operational.